A Review on Greensand Reservoirs' Petrophysical Controls - Navarro Pérez, Daniela Josefina; Fisher, Quentin; Lorinczi, Piroska; Arauna, Anibal Velasquez; Puerto, Jose Valderrama (My University, 2025)
This review provides a comprehensive analysis of the petrophysical controls influencing greensand reservoirs, with an emphasis on the role of glauconite and associated clay minerals in determining porosity, permeability, and water saturation. Greensands contain iron-rich clay minerals that exert paramagnetic and conductive effects, challenging conventional well-log interpretations and often leading to biased estimates of reservoir parameters. Several challenges for petrophysical property measurements are faced in the laboratory due to clay-induced pore-throat obstruction and microporosity, which underscores the importance of tailored interpretation workflows and data integration. In this paper we highlight the necessity of integrated approaches such as combining core analysis, spectral gamma-ray, and nuclear magnetic resonance (NMR) logging with conventional well logs to calibrate petrophysical models using shale-sand water saturation models, such as Waxman-Smits and Simandoux, to better characterise economical pay zones. Finally, future research directions are indicated, which include refining the calibration of saturation and permeability models, advancing rock-typing methodologies, and understanding mineralogical influences on reservoir quality to optimise hydrocarbon recovery from greensand reservoirs.
Keywords: greensand reservoir; glauconite; clay minerals; petrophysical properties